Growth and development in the Iberian Peninsula: three essays - Castro de Oliveira, Emanuel (Kansas State University, 2009)
Although geographic proximity is not enough to imply similar social, political and economic outcomes, the Portuguese and Spanish development experiences have been quite alike since the 15th century and in particular during the post-WWII period. Since 1950, both countries went through significant market transformations, ranging from democratization to market liberalization and adhesion to the European Union. However, even today, these economies, and in particular Portugal, do not rival those of the more developed European countries. This dissertation contributes to the growing body of literature on the Iberian economies by presenting three essays that employ modern macroeconomics tools to further our understanding about the growth and development experiences of these countries. The first essay provides a detailed growth accounting exercise and reconciles the results with the political and socioeconomic context of the 1950-2004 period. Since Total Factor Productivity is identified as the main engine of growth, the second essay explores a quantitative measure for the level of barriers that each country faced in the process of adopting new technologies. The numerical experiments suggest that Spain had consistently lower barriers than Portugal and that the gap has been increasing since the establishment of the European Single Market. The last essay investigates the role of fiscal policy and, specifically, if distortionary taxes on capital and labor income may have been a key factor behind the observed volatility for factor inputs. The simulation results derived from several potential scenarios support this conjuncture. Additionally, the last essay contributes by offering a time series for the levels of effective tax rates on labor and capital income in the Iberian economies over the 1975-2004 period.
Keywords: Economic development; Growth accounting; Technology barriers; Effective tax rates; Portugal; Spain; Economics, General (0501); Economics, Theory (0511)